VIOLATION ON MAXIM OF COOPERATIVE PRINCIPLE IN THE SLOGAN - Permadi, Fery Erga (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2019)
This study argued that violation on maxim of cooperative principle occurs in various type of communication such as in the slogan. This study uses theory from Grice about cooperative principle as main theory and theory about pragmatic context from Cipollone as supporting theory to analyze the data. Based on Grice, violation on maxim of cooperative principle divides into four; violation one maxim, two, three, and four. Cipollone divides pragmatics context into physical context, linguistic, social, and epistemic. In this study, descriptive analysis method is used in analyzing the data. This study is expected can help to understand the strategy of creating slogan that uses violation on maxim of cooperative principle. The result of this study shows that each violation causes other violation as occurs in the violation on maxim of relevance, which is triggered by violation on maxim of quantity.